Association Between Learning Capabilities and Practice-Related Activation Changes in Schizophrenia - Koch, Kathrin (Oxford University Press, 2010)
The present functional magnetic resonance imaging study investigated the neural correlates of practice-associated activation changes in patients with schizophrenia and their association with symptom severity. A group of patients (n = 24) were divided into more successful and less successful learners and were asked to perform a verbal overlearning task in the scanner. We found that both patient groups profited from practice, showing significant decreases in mean response times as well as significant learning-related decreases in cerebral activation. Direct comparison between groups yielded a relative hyperactivation in the group of the less successful learners at the beginning of practice, which showed a reduction with increasing practice. This was reflected by relatively stronger signal decreases in a predominantly fronto-parieto-cerebellar network. In the group of less successful learners, there was a negative correlation between general symptom scores and learning-related signal decreases in a task-relevant network involving cerebellar, inferior and middle frontal (BA 45/47, 46), superior parietal (BA 31), and superior temporal (BA 39) regions. Present data indicate that hyperactivity under high task demands might serve to identify those patients with less potential to profit from practice. However, at least in the context of moderate– to low–working memory demands, this activation abnormality seems to constitute a state rather than a trait characteristic, which patients manage to reduce by successful short-term learning. The findings also suggest that successful learners can better compensate potentially interfering effects exerted by disorder-related psychopathology.